Chicka Chicka Ho Ho Ho - Boniface, William; Chung, Julien ([Place of publication not identified] : Beach Lane Books, 2024)
"In this holiday alphabet rhyme, the crew of beloved Chicka Chicka letters get their chance to shine as decorations on the Christmas tree"--.
new kids book 2024 fall.
Keywords: Christmas; Alphabet; Picture books; Stories in rhyme; Christmas & Advent; Sounds; Holidays & Celebrations; Shapes; Colors